Designs for animal experiments under two-way blocking structure in the presence of systematic trend - BHOWMIK, ARPAN; VARGHESE, ELDHO; JAGGI, SEEMA; YADAV, SUNIL KUMAR (The Indian Journal of Animal Sciences, 2018)
Designs under two-way blocking structure are quite useful in animal experiments. Further, in animal experiments, situations are also quite prevalent where there are evidences of systematic trend component influencing the response. These effects are generally neglected but they may have significant impact on the precision of the experiments, if considered. Suitably choosing a design will nullify the effect of such systematic trend. The present article describes the model under two-way blocking structure incorporating systematic trend component. The condition to nullify the effects of trend component when they are present in the experimental material has been obtained and illustrated under a two-way blocking structure. The analytical procedure has been explained through a hypothetical dataset to show the significance of such effects. The results shows that systematic trend component have significant impact on the precision of the experiments and hence will affect the inference.